Chitinosanase: A fungal chitosan hydrolyzing enzyme with a new and unusually specific cleavage pattern. (15th October 2017) - Kohlhoff, Markus; Niehues, Anna; Wattjes, Jasper; Bénéteau, Julie; Cord-Landwehr, Stefan; El Gueddari, Nour Eddine; Bernard, Frank; Rivera-Rodriguez, Gustavo R.; Moerschbacher, Bruno M.
Highlights: A chitosan-hydrolyzing enzyme with unprecedented cleavage specificity is described. Its hydrolysis products with specific DP and FA have a defined acetylation-pattern. Unusual cleavage specificity makes the enzyme valuable for fingerprinting analyses. Abstract: The biological activities of partially acetylated chitosan oligosaccharides (paCOS) depend on their degree of polymerization (DP), fraction of acetylation (FA ), and potentially their pattern of acetylation (PA ). Therefore, analyzing structure-function relationships require fully defined paCOS, but these are currently unavailable. A promising approach for obtaining at least partially defined paCOS is using chitosanolytic enzymes. Here we purified and characterized a novel chitosan-hydrolyzing enzyme from the fungus Alternaria alternata possessing an absolute cleavage specificity, yielding fully defined paCOS. It cleaves specifically after GlcN-GlcNAc pairs and is most active towards moderately acetylated chitosans, but shows no activity against fully acetylated or fully deacetylated substrates. These unique properties match neither those of chitinases nor chitosanases. Therefore, the enzyme represents the first member of a new class of chitosanolytic enzymes that will allow for the production of fully defined paCOS. Additionally, it represents a highly valuable tool for fingerprinting analyses of chitosan polymers.